Where orang utans see us in cages - Abd Razak, Dzulkifli (2009)
PENANGITES are in for an exciting time. Even before the proposed "tiger ecopark" can take off, the Island is already echoing with roars heard right across the nation. Some of them are loud and desperate enough, like that of a hungry tiger, which could send shivers down the spine. All this in the name of tourism. While the roaring and uproar will continue for some time, quietly, on another less noticed island, the country's first and only orang utan island is making a name for Malaysia. Interestingly, this is not being done to pander the beall and endall of tourism, often at the expense of the locals.